Functional health of the elderly in abuse of alcohol and other drugs (Research, Society and Development, 2020)
Aging can be understood as a natural process of progressive decrease in functionality, which when associated with the abusive use of alcohol and other drugs affects dimensions of the individual's life, with morbidity and mortality. Objective: to describe the functional health profile of the elderly in a Psychosocial Care Center for Alcohol and Other Drugs III, from 2011 to 2018. This is a cross-sectional, descriptive study. The research was carried out in two stages: in the first, it consisted of documentary analysis in 143 medical records and in the second, an interview was applied to collect functional health data with 10 elderly people. The results showed a sociodemographic profile in the majority of males, separated, with elementary education, unemployed, who abuse multiple drugs, and with an absence of dysfunctionality in the components of function and structure, mild impairment in activities and participation and significant facilitators in the environment. It concludes the relevance of investing in care with a focus on functionality and disability in health, making it possible to propose therapeutic strategies that respond to the real demands of the elderly and treatment effectiveness.